Differences in coping strategies among young adults and the elderly with cancer. Issue 5 (5th February 2019) - Hernández, Raquel; Calderon, Caterina; Carmona‐Bayonas, Alberto; Rodríguez Capote, Alejandra; Jara, Carlos; Padilla Álvarez, Airam; Gómez‐Camacho, María de las Nieves; Beato, Carmen; Castelo, Beatriz; Majem, Margarita; Muñoz, María del Mar; Ivars, Alejandra; et al.
Abstract : Background: Coping with cancer and the oncologist–patient relationship can vary depending on the patient's age. Our aim is to examine and compare young and elderly adults with non‐metastatic, resected cancer. Methods: Two groups of patients were selected, young (< 40 years) and elderly (> 70) with a diagnosis of non‐metastatic, resected cancer requiring adjuvant chemotherapy from a pre‐exiting, national database (NEOCOPING Study). Epidemiological variables were collected and subjects' emotional responses, perceptions of the physician–patient relationship, support network, fears, and regret about the decision to receive chemotherapy were assessed with questionnaires validated in previous studies: Mini‐Mental Adjustment to Cancer, Brief Summary Inventory (18 items), European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire‐C30, Shared Decision‐Making Questionnaire‐Physician's version, Shared Decision‐Making Questionnaire‐Patient's version, and Informed Risk (physician and patient versions). Results: Data from 46 young and 46 elderly participants were collected. The most common neoplasms in both groups were breast (50%) and colorectal (22%). The younger adults had a higher level of education and were actively employed (72% vs. 7%). The leading coping strategy in the younger cohort was hope, and resignation among the elderly. Young adults sought more social support and the impact of diagnosis was more negative for them than for older individuals. No significant differences were detected in quality of life; both age groups demanded more time at their first visit with the doctor, while the older group exhibited greater satisfaction with shared decision‐making. At the end of adjuvant chemotherapy, neither age group regretted their decision to receive said treatment. Conclusion: Higher levels of education, greater demands of the labour market, and the advent of the age of information have entailed drastic changes in the physician–patient relationship paradigm. This is especially true in the younger cancer patient population, who require more information and active participation in decision‐making, can display more anxiety about their diagnosis, but also greater capacity to fight.